Genome transfer for the prevention of female infertility caused by maternal gene mutation. (20th June 2020) - Bai, Dandan; Sun, Jin; Jia, Yanping; Yin, Jiqing; Zhang, Yalin; Li, Yanhe; Gao, Rui; Du, Xiling; Li, Kunming; Lin, Jiaming; Tu, Zhifen; Wang, Yu; et al.
Abstract: Poor oocyte quality is associated with early embryo developmental arrest and infertility. Maternal gene plays crucial roles in the regulation of oocyte maturation, and its mutation is a common cause of female infertility. However, how to improve oocyte quality and develop effective therapy for maternal gene mutation remains elusive. Here, we use Zar1 as an example to assess the feasibility of genome transfer to cure maternal gene mutation–caused female infertility. We first discover that cytoplasmic deficiency primarily leads to Zar1- null embryo developmental arrest by disturbing maternal transcript degradation and minor zygotic genome activation (ZGA) during the maternal-zygotic transition. We next perform genome transfer at the oocyte (spindle transfer or polar body transfer) and zygote (early pronuclear transfer or late pronuclear transfer) stages to validate the feasibility of preventing Zar1 mutation–caused infertility. We finally demonstrate that genome transfer either at the oocyte or at the early pronuclear stage can support normal preimplantation embryo development and produce live offspring. Moreover, those pups grow to adulthood and show normal fertility. Therefore, our findings provide an effective basis of therapies for the treatment of female infertility caused by maternal gene mutation.